Perlindungan Hukum bagi Kreditur dalam Kontrak yang Melibatkan Jaminan Fidusia - Revian Jedha Arhansyah; Hikam Firmansyah; Ifyar Aztyardi Anhar; Mohamad Febri Pribadi; Zhafif Hylmi Yulianto (Universitas Wahid Hasyim, 2024)
This research analyzes the defence of creditors legally under credit agreements containing fiduciary assurances. A fiduciary guarantee gives the creditor a security right over an object that remains in the debtor's possession. The purpose of this research is to evaluate the application and problems of legal protection against the debtor in the context of the agreement. The study method adopted was normative juridical, with a statute and case-based approach. The results show that legal protection of debtors can be seen from material and formal aspects. The material aspect involves the balance of rights and obligations between the creditor and the debtor, the limitation of the value of the fiduciary guarantee, and the dispute resolution mechanism. Meanwhile, the formal aspects include notarial deeds, registration, and fiduciary guarantee certificates. Problems that arise include misuse of the collateral by the debtor, disputes over the rights to the collateral, mismatch between the value of the collateral and the debt, and difficulties in determining the location of the collateral.. It is hoped that this research will contribute to the development of legal knowledge, provide feedback to associated parties., and offer solutions to problems faced in the context of fiduciary assurances attached to credit agreements.